Factors Determining Employee Satisfaction - A Case Study of Public Sector Organizations in Jammu Region - Sharma, Parul; Gupta, Meenakshi (Prabandhan: Indian Journal of Management, 2009)
The present paper throws attention on the factors influencing the job satisfaction level of the employees of the various public sector organizations. The study is based mainly on the primary data collected from employees with the help of a well drafted pre tested structured questionnaire. Factor analytical approach has been applied on the responses of 150 employees to identify the factors, which determine employees' satisfaction in order to condense the information contained in a number of original variables into a smaller set of dimensions (factors) with a minimum loss of information. To have more clarity in factor solution and to reduce the inaccuracies, rotation along with the varimax method of rotation of factors was used. However, before applying factor analysis the data adequacy tests for factor analysis were carried out. Principal component analysis was used for extracting factors and the number of factors to be retained was based on the latent root criterion i.e. Eigen values greater than 1. The results were obtained through Orthogonal Rotation with Varimax and all factor loadings 0.40 or higher (ignoring signs) were retained). The factors have been restricted to eleven statements for rotation purposes in order to condense the data.